Ricerca scientifica e promozione accademica in Medicina del lavoro: quali sono le regole del gioco? / Scientific research and academic promotion in Occupational Medicine: what are the rules of the game? - Franco, G. (La Medicina del Lavoro, 2011)
«Scientific research and academic promotion in Occupational Medicine: what are the rules of the game?». Introduction: Recently, the National University Council (CUN) recognized the importance of bibliometric indicators in assessing scientific output and the Ministry of Education, University and Research established that the selection committees’ decision must be guided by internationally recognized metrics  including the impact factor (IF). Aim: To analyse methods and tools of metrics to assess scientific performance in Occupational Medicine by examining some critical aspects for entry-level positions and academic promotion in the Universities. Methods: By means of different databases (Web of Knowledge®, Scopus®, SCImago), the h-index was studied to assess the scientific output in the field of Occupational Medicine. The h-index was used as an index of both output and quality of overall output of researchers, disciplines, journals, and countries. Results: Italian scientific output in the Public, Environmental & Occupational Health subject category (h-index=62) was lower than almost the total of other medical disciplines and, at an international level, is ranked at 12th place (other disciplines ranked 3rd to 9th). Output was 32% compared to that of the USA (other disciplines ranged from 42% and 61%). However, it should be noted that most scientific papers of Occupational Medicine researchers are published mainly in journals of different disciplines (with a higher IF) rather than in journals of Public, Environmental & Occupational Health (with a lower IF). Conclusion: Assuming that selection committees’ decisions will be guided by metrics and will respect the minimum standard proposed by CUN, Occupational Medicine researchers aiming at academic promotion will have good reason to ask themselves not only which journals are most useful but also which journals have the greatest impact. This fact could have profound implications for the future of the discipline.